Assessing Contraceptive Service Training Using the Kirkpatrick Model to Improve Health Worker Competency - Prawitasari, Shinta; Barirah, Ratih; Sangun, Diannisa Ekarumi Enisar; Wiyati, Putri Sekar (Indonesian Journal of Obstetrics and Gynecology, 2026)
AbstractObjective: To evaluate contraceptive service training using the Kirkpatrick evaluation model levels 1–3.Methods: This quasi-experimental study was conducted based on the Kirkpatrick evaluation model to assess contraceptive service training in West Nusa Tenggara, Indonesia. Thirty health workers participated after providing informed consent. The competency-based training employed a blended learning approach, consisting of 57 hours of online theoretical instruction followed by 50 hours of face-to-face practical training. The training was evaluated at the reaction, learning, and behavior levels of the Kirkpatrick model. Participants were representatives from districts and municipalities across West Nusa Tenggara Province.Results: Participants reported a high level of satisfaction with the training (86.89%). Knowledge levels improved significantly, with mean scores increasing from 56.33 on the pre-test to 95.73 on the post-test. During the training, participants demonstrated effective counseling skills as well as competency in IUD and implant insertion and removal. However, the mean competency scores showed a decline one year after the training.Conclusion: The improvement in pre-test and post-test scores was statistically significant (p < 0.001). At the behavior level, a slight decrease in competency was observed after one year of follow-up.Keywords: contraceptive services, contraceptive training, evaluation, health worker, kirkpatrick model.